Umbilical Cord‐Mesenchymal Stromal Cell‐Derived Extracellular Vesicles Target the Liver to Improve Neurovascular Health in Type 2 Diabetes With Non‐Alcoholic Fatty Liver Disease - Minghao Du; Hao Yang; Jinyun Niu; Jing Huang; Lihong Wang; Junxiu Xi; Panpan Meng; Zhiyong Liu; Guaiguai Ma; Jiani Li; Xiaoyan Liu; Liang Guo; et al. (Journal of Extracellular Vesicles)
ABSTRACT Type 2 diabetes mellitus (T2DM) combined with non‐alcoholic fatty liver disease (NAFLD) exacerbates metabolic dysregulation and neurovascular complications, presenting significant therapeutic challenges. We demonstrate, using SPECT/CT imaging, that extracellular vesicles (EVs) from mesenchymal stromal cells (MSCs) predominantly accumulate in the liver, where they deliver miR‐31‐5p to suppress platelet‐derived growth factor B (PDGFB) produced by hepatic macrophages. This intervention impedes NAFLD progression and establishes a mechanistic link between liver repair and neurovascular improvement. Specifically, single‐nucleus RNA sequencing reveals that PDGFB suppression enhances hippocampal pericyte recovery via the PDGFB‐PDGFRβ axis and orchestrates the activation of growth differentiation factor 11 (GDF11), thus promoting neuroplasticity. Furthermore, AAV injections indicate that hepatic PDGFB modulation recalibrates transthyretin (TTR) dynamics, thereby restoring its neuroprotective functions and preventing its pathological deposition in the brain. These findings position MSC‐EVs as a transformative therapeutic platform that leverages the liver‐brain axis to address the intertwined metabolic and neurovascular complications of T2DM, offering a promising avenue for clinical translation.